Nanofibrous spongy microspheres to deliver rabbit mesenchymal stem cells and anti-miR-199a to regenerate nucleus pulposus and prevent calcification. (October 2020) - Feng, Ganjun; Zhang, Zhanpeng; Dang, Ming; Rambhia, Kunal J.; Ma, Peter X.
Abstract: Lower back pain is mainly caused by intervertebral disc degeneration, in which calcification is frequently involved. Here novel nanofibrous spongy microspheres (NF-SMS) are used to carry rabbit bone marrow mesenchymal stromal cells (MSCs) to regenerate nucleus pulposus tissues. NF-SMS are shown to significantly enhance the MSC seeding, proliferation and differentiation over control microcarriers. Furthermore, a hyperbranched polymer (HP) with negligible cytotoxicity and high microRNA (miRNAs) binding affinity is synthesized. The HP can complex with anti-miR-199a and self-assemble into "double shell" polyplexes which are able to achieve high transfection efficiency into MSCs. A double-emulsion technique is used to encapsulate these polyplexes in biodegradable nanospheres (NS) to enable sustained anti-miR-199 delivery. Our results demonstrate that MSC/HP-anti-miR-199a/NS/NF-SMS constructs can promote the nucleus pulposus (NP) phenotype and resist calcification in vitro and in a subcutaneous environment. Furthermore, injection of MSC/HP-anti-miR-199a/NS/NF-SMS can stay in place, produce functional extracellular matrix, maintain disc height and prevent intervertebral disc (IVD) calcification in a rabbit lumbar degeneration model.